Thermophilic Water Gas Shift Reaction at High Carbon Monoxide and Hydrogen Partial Pressures in Parageobacillus thermoglucosidasius KP1013 - Daniel Barón Díaz; Anke Neumann; Habibu Aliyu (Fermentation, 2022)
The facultatively anaerobic Parageobacillus thermoglucosidasius oxidizes carbon monoxide to produce hydrogen via the water gas shift (WGS) reaction. In the current work, we examined the influence of carbon monoxide (CO) and hydrogen (H2) on the WGS reaction in the thermophilic P. thermoglucosidasius by cultivating two hydrogenogenic strains under varying CO and H2 compositions. Microbial growth and dynamics of the WGS reaction were monitored by evaluating parameters such as pressure, headspace composition, metabolic intermediates, pH, and optical density. Our analyses revealed that compared to the previously studied P. thermoglucosidasius strains, the strain KP1013 demonstrated higher CO tolerance and improved WGS reaction kinetics. Under anaerobic conditions, the lag phase before the WGS reaction shortened to 8 h, with KP1013 showing no hydrogen-induced product inhibition at hydrogen partial pressures up to 1.25 bar. The observed lack of product inhibition and the reduced lag phase of the WGS reaction support the possibility of establishing an industrial process for biohydrogen production with P. thermoglucosidasius.